The Research Study of Mind Persuasive Techniques in Lecture of Phra Phrommanggalājāraya (Ven. Paññānanda Bhikkhu) - ดีเลิศ, วิระวัลย์ (Thai Interdisciplinary and Sustainability Review, 2019)
The research study of mind persuasive techniques in lecture of Phra Phrommanggalājāraya (Ven. Paññānanda Bhikkhu) is a qualitative research. This study can be divided into two parts as follows: 1.The lecture components: the title contains words about Buddhism and the introduction begins with the origin or cause of the issue. The story is to focus on the content and the subject. A summary of the four elements show the most vision. 2. Strategies of mind persuasion in lecture with all three strategies found that the 3rd strategy shows the persuasion as refer to proverbs of Buddhist and helps attract ion and keep audiences interested.